Neurofibromatosis type 1‐associated malignant peripheral nerve sheath tumour carcinomatous pleurisy: an autopsy case - Marie Furukawa; Hiroki Ota; Yasuhiko Nakamura; Yasuhiro Nihonyanagi; Naobumi Tochigi; Sakae Homma (Respirology Case Reports, 2019)
A 57‐year‐old man with neurofibromatosis type 1 (NF‐1) and intrathoracic meningoceles was admitted to hospital after presenting with neck pain and progressive dyspnoea. On admission, a chest computed tomography scan demonstrated right pleural effusion, neck tumour, intrathoracic meningoceles, and rib metastasis. The myelography showed no transportation between the intrathoracic meningoceles and pleural cavity. As a result, these radiological finding indicated the potential for malignant transformation. The appearance of the right pleural effusion was bloody and had no malignant cells. We biopsied the neck tumour, and the tissue showed glass‐like materials but no malignant cells. At 1 month after admission, he developed bladder–rectal disorder, syndrome of inappropriate secretion of antidiuretic hormone, and paralysis of both legs and later died. An autopsy demonstrated glass‐like material in the neck tumour, which was surrounded by malignant cells. NF‐1 appears to have progressed to a malignant peripheral nerve sheath tumour in this patient.